PENERAPAN PEMBELAJARAN ETNOMATEMATIKA MASJID AGUNG TUBAN UNTUK MENINGKATKAN KEMAMPUAN BELAJAR SISWA KELAS V MATERI VOLUME BALOK MELALUI KUBUS SATUAN - Rena Fadlilah Rahmawati; Julianto; Anita Kurniasari; Vivi Adrianti; Fitria Hidayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Ethnomathematics, or the integration of cultural elements in Mathematics learning, provides an important contribution for students. In the midst of continuous progress, the existence of culture is often overlooked. Therefore, the solution to this problem is to insert regional cultural elements into Mathematics learning. The aim of this research is that students can identify the historic building of the Tuban Great Mosque to improve student learning outcomes on block volume material and can make a mosque tower from several cubes and then determine the block volume using unit cubes. The research method used is Classroom Action Research (PTK), with a Realistic Mathematic Education (RME) approach. The results of the research show that students succeeded in overcoming the challenges of building a mosque tower and calculating the volume of blocks using unit cubes correctly, as well as identifying mathematical concepts in the Tuban Great Mosque.